Proactive Resilience through Architectural Hybridization - Sousa, Paulo (2009)
Recently, we presented a theoretical Physical System Model (PSM), which introduced a new dimension over which distributed systems resilience may be evaluated - exhaustion-safety. We showed that it is theoretically impossible to have an exhaustion-safe f fault/intrusion-tolerant asynchronous system, even when enhanced with asynchronous proactive recovery. This paper proposes proactive resilience as a new and more resilient approach to proactive recovery based on architectural hybridization. We present the Proactive Resilience Model (PRM) and describe a design methodology under the PRM. This design methodology is formally proved to be a way of building exhaustion-safe systems and we use it to derive an exhaustion-safe distributed f fault/intrusion-tolerant secret sharing system